2002
DOI: 10.1095/biolreprod67.2.546
|View full text |Cite
|
Sign up to set email alerts
|

Polo-Like Kinase-1 Is a Pivotal Regulator of Microtubule Assembly During Mouse Oocyte Meiotic Maturation, Fertilization, and Early Embryonic Mitosis1

Abstract: Polo-like kinases (Plks) are a family of serine/threonine protein kinases that have been activated through phosphorylation. The activity of these kinases has been shown to be required for regulating multiple stages of mitotic progression in somatic cells. In this experiment, the changes in Plk1 expression were detected in mouse oocytes through Western blotting. The subcellular localization of Plk1 during oocyte meiotic maturation, fertilization, and early cleavage as well as after antibody microinjection or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 34 publications
9
90
0
Order By: Relevance
“…The mice with color gene type of aabbcc were from an inbred strain of Kunming white mice, a native breed widely used in biological research in China. 35 Ovaries were removed from 4-6 week-old female mice at 46-48 hours after PMSG injection. Prophase-stage oocytes displaying a germinal vesicle (GV) without cumulus cell masses were released from ovarian follicles and collected in M2 medium supplemented with 0.2 µM (IBMX) which prevented germinal vesicle breakdown (GVBD).…”
Section: Materials and Methordsmentioning
confidence: 99%
“…The mice with color gene type of aabbcc were from an inbred strain of Kunming white mice, a native breed widely used in biological research in China. 35 Ovaries were removed from 4-6 week-old female mice at 46-48 hours after PMSG injection. Prophase-stage oocytes displaying a germinal vesicle (GV) without cumulus cell masses were released from ovarian follicles and collected in M2 medium supplemented with 0.2 µM (IBMX) which prevented germinal vesicle breakdown (GVBD).…”
Section: Materials and Methordsmentioning
confidence: 99%
“…After taxol treatment, septin2 disappeared from spindle fibers and translocated to the region around chromosomes. Importantly, localization of septin2 differs from other proteins involved in spindle formation that we previously studied (e.g., MDK, 43 BARC1, 44 and PLK1, 45 ), which are present at the center of microtubule organizing centers (MTOCs) after taxol treatment, participating in microtubule nucleation or organization. Moreover, it is reported that septins regulate microtubule dynamics through MAP4.…”
Section: Resultsmentioning
confidence: 91%
“…After Syt1-MO knockdown, γ-tubulin failed to congress at the spindle poles but irregularly dispersed around the deformed spindles and redistributed into the oocyte cytoplasm. Therefore, it is clear that Syt1 distribution changes are similar to those of many MTOC-associated proteins, such as NEDD1, 32 Polo-like kinase1(Plk1) 33,34 and Astrin, 18 indicating a high level of correlation between Syt1 and the MTOC.…”
Section: Resultsmentioning
confidence: 95%